New insight into the applicability of spectroscopic indices for dissolved organic matter (DOM) source discrimination in aquatic systems affected by biogeochemical processes. (15th December 2018) - Lee, Mi-Hee; Osburn, Christopher L.; Shin, Kyung-Hoon; Hur, Jin
Abstract: Despite numerous studies on changes to optical proxies of dissolved organic matter (DOM) by biogeochemical processing, the applicability of commonly-used spectroscopic indices has not been explored as DOM source tracking tools under conditions where biogeochemical processes may alter them. For this study, two contrasting DOM end members, Suwannee River fulvic acid (SRFA) and algogenic DOM (ADOM), and their mixtures, were used to examine the potential changes in the conservative mixing behaviors of several well-known optical indices via end member mixing analysis under the influence of biodegradation, UV irradiation, and clay mineral (kaolin) adsorption. Most of the source tracking indices exhibited large deviations from conservative mixing behavior between the two end-members. Biodegradation tended to lower the portions of labile and ADOM in the mixtures, while the allochthonous end member (SRFA) was reduced by a greater extent after the process of UV irradiation or adsorption. The extent of the variations in biological index (BIX) and fluorescence index (FI) was smaller for more allochthonous DOM mixtures under the processes of biodegradation and UV irradiation. Overall, the process-driven variations in ratios of humic-like: protein-like fluorescence (as modeled by parallel factor analysis, PARAFAC) were greater for the SRFA versus ADOM. Evaluation criteria used in this study suggested that BIX, specific UV absorbance (SUVA), and FI each could be the reliable discrimination parameter least affected by biodegradation, UV irradiation, and adsorption, respectively. This study provided criterion information for the choice and the interpretation of the optical indices for DOM source discrimination in aquatic environments after substantial biogeochemical processing. Graphical abstract: Highlights: Potential changes in optical indices by biogeochemical processes are examined. Most indices showed large deviations from the prediction based on ideal mixing. BIX and SUVA were robust indices under bio-and photo-degradation, respectively. It provides new insight into indices' applicability under biogeochemical processes.